2019
DOI: 10.17582/journal.aavs/2019/7.11.1021.1034
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Resistant Enterococcus: Issues in Human Health, Animal Health, Resistant Mechanisms and the Malaysian Paradox

Abstract: E nterococcus occur naturally in the surroundings and are an important constituents of the gut microbes in humans and animals (van Schaik and Willems, 2010; Boehm and Sassoubre, 2014). Enterococcus species detected till date are over 50 (Bonacina et al., 2016; Guzman et al., 2016). In human guts, Enterococcus faecalis occur mostly followed by E. faecium while in livestock, E. faecium is the major species followed by E. faecalis, E. cecorum and sometimes E. hirae (Klein, 2003; Guzman et al., 2016). Urinary trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…All three hospitals, including UMMC in this study, are located in Klang Valley within close proximity of each other. Previous studies reported a greater prevalence of the van A gene among Malaysian VRE strains isolated from various sources, including humans, farmed animals, and even within the natural environment [ 18 , 19 ]. However, we observed that the van B gene occurred more frequently in the VRE strains identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…All three hospitals, including UMMC in this study, are located in Klang Valley within close proximity of each other. Previous studies reported a greater prevalence of the van A gene among Malaysian VRE strains isolated from various sources, including humans, farmed animals, and even within the natural environment [ 18 , 19 ]. However, we observed that the van B gene occurred more frequently in the VRE strains identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The virulence factors of enterococci play a major role in the pathogenicity of enterococci and could be explained not only by the presence of virulence determinants; antibiotic resistance genes play an important role in the pathogenicity of enterococcal strains (15,16). In vivo and on medical devices biofilm formation aids disease development as it boosts the persistence infections and reduces antimicrobial activity (17).…”
Section: Discussionmentioning
confidence: 99%
“…Human antimicrobial use, as well as their use as growth promoters in the livestock industry, were thought to have resulted in the emergence of enterococcal-resistant strains. A good example is the use of avoparcin as a feed additive to promote livestock growth [ 3 ].…”
Section: Introductionmentioning
confidence: 99%